Republic of Mozambique : 2007 Article IV Consultation, Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criterion, Financing Assurance Review, and Request for a Three-Year Policy Support Instrument; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Mozambique. (IMF Staff Country Reports; Country Report, 2007)
This paper discusses the Republic of Mozambique's 2007 Article IV Consultation and Sixth Review Under the Poverty Reduction and Growth Facility (PRGF). The post-conflict rebound has largely run its course, and first-generation reforms are completed; a second wave of reforms is needed to sustain broad-based growth and further reduce poverty. Achieving the non-income-related Millennium Development Goals also requires scaling up basic services without undermining macroeconomic stability. The PRGF program helped maintain macroeconomic stability in the face of exogenous shocks and addressed the structural weaknesses identified in the Ex Post Assessment.